Interaction Solutions of Long and Short Waves in a Flexible Environment - Akturk, Tolga (Alexandria engineering journal, 2020)
In this study, the new traveling wave solutions resulting from the interaction of the long-short wave system were obtained by using the exp-function method. Two and three dimensional graphs of the obtained solutions were drawn by selecting the appropriate parameters. Density graphs of the solution functions were obtained and the interaction of the waves was observed.